2008
DOI: 10.1177/1934578x0800300318
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Cytotoxic Cycloartanes from Guayule (Parthenium Argentatum)

Abstract: The need for the discovery and development of new pharmaceuticals for the treatment of cancer demands that all approaches to drug discovery should be exploited. Among the possible approaches, the one from natural products has made many unique and vital contributions to drug discovery. This mini review focuses on researches made in our laboratory on cycloartanes isolated from Parthenium argentatum, as well as some of its derivatives, in order to obtain potential anti-inflammatory and anti-cancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The stated objective (identifying and quantifying all components of the same resin) is mostly achieved: less than 5% of compounds remain unqualified and quantified. Knowing the composition of guayule resin and the quantity of each molecule is of great interest as many of them have a high added value: guayulins have shown repellent and anti-feedant activities 33 and argentatins could be used in cancer treatments 6 . The aim is now to extract and fractionate this resin to valorise it.…”
Section: Discussionmentioning
confidence: 99%
“…The stated objective (identifying and quantifying all components of the same resin) is mostly achieved: less than 5% of compounds remain unqualified and quantified. Knowing the composition of guayule resin and the quantity of each molecule is of great interest as many of them have a high added value: guayulins have shown repellent and anti-feedant activities 33 and argentatins could be used in cancer treatments 6 . The aim is now to extract and fractionate this resin to valorise it.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies indicated that the formation of an unsaturated bond conjugated to the carbonyl group at C3 and the incorporation in ring A of nitrile, formyl, and bromine substituents increases the cytotoxicity of the molecule. [7] Cycloartane triterpenoids are known to have multiple medicinal properties, such as antiviral, [8] anti-tumor, [9] antiparasite, [10] and anti-inflammatory [11] activities. Studies have shown that different cycloartane-type triterpene have cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying the A‐ring of argentatins A and B has resulted in analogs with improved cytotoxic activity against certain cancer cell lines. The results of these studies indicated that the formation of an unsaturated bond conjugated to the carbonyl group at C3 and the incorporation in ring A of nitrile, formyl, and bromine substituents increases the cytotoxicity of the molecule [7] …”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids including incanilin, guaianolides, ambrosin, coronopilin, anhydrocoronopilin and argentatins have been isolated from plants of the genus Parthenium (Romo de Vivar & Matsubara, 1986), and a number of argentatins and other cycloartane‐type triterpenes have been encountered in guayule ( Parthenium argentatum ) resin (Powell, 1998). Previous studies have shown that argentatins A and B have anti‐microbial (Parra‐Delgado, Garcia‐Pillado, et al, 2005) and anti‐inflammatory (Flores‐Rosete & Martínez‐Vázquez, 2008) properties and cytotoxic activity against several cancer cell lines (Parra‐Delgado et al, 2006; Parra‐Delgado, Garcia‐Pillado, et al, 2005; Parra‐Delgado, Ramirez‐Apan, & Martinez‐Vazquez, 2005). However, there have been no reports of anti‐nociceptive properties for any argentatins.…”
Section: Introductionmentioning
confidence: 99%